Collaboration Strategy for Educational Service Delivery at the Regional Coordinator Office for Education and Culture in Purworejo District - Riska Wirawan; Wirid Winduro (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This research aims to analyze collaboration strategies in educational services and identify the challenges and implications of implementing collaborative governance at the District Education and Culture Regional Coordinator Office (Korwilcambidik) in Bener District, Purworejo Regency. The research method used is descriptive qualitative, with data collection techniques including interviews, observation, and document study. The research findings indicate that cross-sector collaboration between government, educational institutions, and the community serves as an adaptive strategy for improving the effectiveness of public services in the field of education. Although the collaboration has been successful, there are still obstacles such as the lack of a formal legal basis, low levels of trust between agencies, and differences in interests and limited resources. Factors such as collaborative leadership, open communication, and community participation play an important role in maintaining the sustainability of cross-sectoral cooperation. This research concludes that the implementation of collaborative governance in the education sector has the potential to become an effective, transparent, and sustainable model of government governance if supported by institutional commitment and a trust-based work culture.